Theological practices that matter - Bloomquist, Karen L. (Theology in the life of the church, 2009)
Some participants in the concluding consultation of the Theology in the Life of the Churches program reflect theologically on such diverse practices as reading the Bible; worship; baptism; forgiveness of sin; church discipline; inclusion of children at the Eucharist; spiritual care of the dying; stigmata as marks of Christ; sexual taboos; engaging political powers; and theological formation in daily life.